Taxonomy of South African ericas (Erica L.) and differentiation of their seeds - Szkudlarz, Piotr (Biodiversity: Research and Conservation, 2006)
The paper presents an attempt of the systematic analysis of 33 species of the Erica genus, originating from the Republic of South Africa. The analysis was based on morphological and anatomical features of seeds, distinguished in the course of the research. As a result, the studied taxa were divided into two distinct groups. One includes almost exclusively species with smooth seeds, the other one - species with reticular and papillae-covered seeds. The obtained division of the taxa is completely different from the systematic divisions of the genus accepted so far.